Activation of Rac1 Has an Opposing Effect on Induction and Maintenance of Long-Term Potentiation in Hippocampus by Acting on Different Kinases - Cui, Dongyang; Jiang, Xiaodong; Chen, Ming; Sheng, Huan; Shao, Da; Yang, Li; Guo, Xinli; Wang, Yingqi; Lai, Bin; Zheng, Ping (Frontiers in Molecular Neuroscience, 2021)
Rac1 is a small GTPase of the Rho family. Previous study showed that the activation of Rac1 had an opposing effect on induction and maintenance of long-term potentiation (LTP) in the hippocampus. However, the molecular mechanism underlying this opposing effect remains to be addressed. In the present work, we find that the activation of Rac1 during the induction of LTP leads to an activation of PKCι/λ by PI3K, whereas the activation of Rac1 during the maintenance of LTP leads to the inhibition of PKMζ by LIMK in the hippocampus. This result suggests that during different stages of LTP, the activation of Rac1 can modulate different signaling pathways, which leads to an opposing effect on the induction and maintenance of LTP in the hippocampus.